FACTORS ASSOCIATED WITH WORK FATIGUE IN GAS STATION OPERATORS IN RANTAU KELOYANG DISTRICT IN 2021 - Intan Widya Sari; Melda Yenni; Eti Kurniawati (Sekolah Tinggi Pariwisata Mataram, 2023)
Work fatigue is one of the health and safety problems that can be a risk factor for accidents at work. One of the main factors causing work accidents caused by humans is stress and fatigue. Work fatigue provides a 50% distribution of the occurrence of work accidents. Gas station is a company that runs the production process continuously for 16 hours of work for 7 days a week. The length of working hours is one of the factors causing work fatigue. The purpose of this study was to determine the factors related to work fatigue in workers at the gas station operator division in Rantau Keloyang District, Bungo Regency in 2021. This study uses a quantitative method using a cross sectional design by providing questionnaires and interviews to gas station workers. For work environment data, the data taken are noise and heat pressure using WBGT and sound level meter (SLM). The results of this study indicate that the factors related to work fatigue are work shifts, nutritional status, noise, and heat stress on work fatigue in workers at the gas station operator division in Rantau Keloyang District. The most frequent distribution of the nutritional status of workers is in the thin category. As well as the distribution of the most noise frequency is the category that does not meet the requirements. It is recommended for gas station operators to maximize break hours to take a short break so that work fatigue can be overcome and work becomes more focused and it is hoped that relevant agencies and gas station owners will make policies to minimize work fatigue and provide personal protective equipment for their workers.